Dose-Response and Substitution Analyzes of Sweet Beverage Consumption and Body Weight in Dutch Adults: The Lifelines Cohort Study - Buso, Marion E. C.; Brouwer-Brolsma, Elske M.; Naomi, Novita D.; Harrold, Joanne A.; Halford, Jason C. G.; Raben, Anne; Feskens, Edith J. M. (Frontiers in Nutrition, 2022)
Background/Methods: Prospective studies investigating sweet beverages and body weight associations show inconsistent results. We examined prospective dose-response associations of sugar-sweetened beverages (SSB), low/no-calorie beverages (LNCB), and fruit juice with body weight-related outcomes among 78,127 Dutch adults followed for 4 years. Baseline intakes were assessed using a validated food-frequency questionnaire (FFQ) with 150 ml representing a standard serving. Outcome variables were body weight change, waist circumference change, overweight/obesity, and abdominal obesity. Associations were investigated by using linear and nonlinear dose-response analysis, as well as substitution models while adjusting for multiple socio-demographic, lifestyle, health, and dietary variables. Results: Participants were 46±13 (mean ±SD) years old and 60% were women. Adjusted dose-response analyses indicated an association between SSB and LNCB, and both body weight (+0.02 kg/y; SE 0.01 and +0.05 kg/y; SE 0.01) and waist circumference changes (+0.04 cm/y; SE: 0.01 and +0.11 cm/y; SE:0.01). Associations for overweight/obesity and abdominal obesity incidence were +3% (95%CI: 1.00-1.06) and +2% (95%CI: 0.99-1.06) for SSB and +8% (95%CI: 1.06-1.11) and +5% (95%CI: 1.03-1.07) for LNCB, respectively. Substitution of SSB with LNCB was associated with higher weight change (+0.04 kg/y), waist circumference change (+0.09 cm/y), overweight/obesity incidence (+6%), but not abdominal obesity incidence. For fruit juice, we observed beneficial associations for intake levels below 1 serving/d with weight, waist circumference change, and overweight/obesity incidence, and no association with abdominal obesity. Subsequent substitution analyses indicated a small beneficial association for the replacement of SSB with fruit juice on weight (-0.04 kg/y) and waist circumference (-0.04 cm/y), but not with other outcomes. Conclusions: Overall, our results suggest that habitual consumption of both SSB and LNCB may adversely affect weight-related outcomes. In contrast, fruit juice consumption <150mL may be beneficial with respect to weight and waist circumference.